2022
DOI: 10.3389/fonc.2022.856963
|View full text |Cite
|
Sign up to set email alerts
|

YY1 Is a Key Player in Melanoma Immunotherapy/Targeted Treatment Resistance

Abstract: Malignant melanoma, with its increasing incidence and high potential to form metastases, is one of the most aggressive types of skin malignancies responsible for a significant number of deaths worldwide. However, melanoma also demonstrates a high potential for induction of a specific adaptive anti-tumor immune response being one of the most immunogenic malignancies. Yin Yang 1 (YY1) transcription factor is essential to numerous cellular processes and the regulation of transcriptional and posttranslational modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 72 publications
(77 reference statements)
0
11
0
Order By: Relevance
“…MiR-3666/KLF7 axis, as the downstream target of KCNQ1OT1, regulate tumor growth ( Huang et al, 2021 ). The zinc finger protein YY1 belongs to the GLI-Kruppel class and is widely distributed throughout the human body ( Kwiatkowska et al, 2022 ). Early growth response protein-1 (EGR1) encodes a zinc finger protein of the EGR family, which is involved in transcriptional regulation ( Wang et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-3666/KLF7 axis, as the downstream target of KCNQ1OT1, regulate tumor growth ( Huang et al, 2021 ). The zinc finger protein YY1 belongs to the GLI-Kruppel class and is widely distributed throughout the human body ( Kwiatkowska et al, 2022 ). Early growth response protein-1 (EGR1) encodes a zinc finger protein of the EGR family, which is involved in transcriptional regulation ( Wang et al, 2021c ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of T-cell exhaustion manifest in decreased proliferation, increased expression of inhibitory checkpoint molecules such as PD-1, impaired production of type I cytokines, and reduced ability to kill antigenic targets [ 101 , 102 , 103 ]. The inactivation of PD-1-expressing CD8 + T cells by PD-L1 inhibits tumor-infiltrating CD4 + /CD8 + T cells (CD4 + /CD8 + TILs) and leads to a decrease in cytokines including tumor necrosis factor-alpha (TNF-α), interferon gamma (IFN-γ), and interleukin 2 (IL-2), allowing cancer cells to escape the immune reaction [ 104 , 105 , 106 , 107 ]. In a study by Baitsch et al [ 101 ], melanoma samples were found to have a majority of their tumor-infiltrating lymphocytes (TILs) exhausted from PD-1 compared to normal T-cell function in non-cancerous skin cells [ 101 ].…”
Section: Role Of the Pd-1/pd-l1 Interaction In The Inactivation Of An...mentioning
confidence: 99%
“…In a study by Baitsch et al [ 101 ], melanoma samples were found to have a majority of their tumor-infiltrating lymphocytes (TILs) exhausted from PD-1 compared to normal T-cell function in non-cancerous skin cells [ 101 ]. It was concluded that upregulation of PD-L1 expression is a mechanism for tumor cells to defend themselves from cell death by cytotoxic T cells [ 104 , 105 , 106 , 107 ] ( Figure 2 ).…”
Section: Role Of the Pd-1/pd-l1 Interaction In The Inactivation Of An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed death receptor-1 (PD-1) and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) are the most common immune checkpoint receptors expressed on the surface of T lymphocytes ( 60 ). YY1 has been shown to positively regulate immune checkpoint receptors such as PD1 and CTLA-4 ( 61 ), and YY1 was upregulated in PD1-positive T cells infiltrating lymphocytes in melanoma tumors and directly regulated the expression of PD1 and LAG3 by binding to the promoter region ( 62 , 63 ). PD-1 is a critical receptor expressed on activated T cells that inhibits T cell-mediated immune responses upon binding to its ligand programmed cell death ligand 1 (PD-L1) ( 64 ).…”
Section: Role Of Yy1 In the Tumor Microenvironmentmentioning
confidence: 99%